Impact of Earned Sick Leave Policy on Worker Wellbeing Across Industries - Hannah I. Rochford; Aurora B. Le (Safety and Health at Work)
Background: Earned sick leave (ESL) policies enable employees to have paid time off to address short-term, individual, or familial health needs. In the U.S., ESL is not federally mandated, but state ESL adoption has increased. Despite this increase, if and how ESL policies impact nonfatal illness/injury reporting by workers remain unknown. Methods: Average treatment effect on the treated estimates of ESL policies were reached using two-way fixed effects and Gardner's two-stage difference-in-differences approach. Annual state rates of occupational nonfatal illness/injury reports were derived from the Bureau of Labor Statistics for each North American Industry Classification. ESL policy data were accessed from Temple University Center for Public Health Law Research's Law Atlas. Results: In states that adopted ESL prior to 2019, two-way fixed effect analyses suggest a marginally significant increase in rates of nonfatal illness/injury reports across industries (+0.064 cases per 100 full-time workers, p = 0.10) following the implementation of ESL policies. Industries with low proportions of insured employees did not experience a change in reported illness/injury following ESL policy adoption. Industries with high proportions of employees with known barriers to care also experienced no change in reported illness/injury post ESL adoption. Conclusion: ESL policy enactment is a promising strategy for improving worker wellbeing by encouraging reporting to employers and foreseeably increasing use of time off for illness/injury recovery. However, results also suggest ESL policies do not benefit all employees to the same extent.